Orthogonally polarized dual-wavelength Nd:GdVO4/Nd:YVO4 laser at 1341 and 1342 nm with adjustable power ratio. - Hao Yu; Yongliang Li; Fahad Moazzam; Lin Lin; Bo Gao (PLoS ONE)
A continuous-wave (CW) orthogonally polarized dual-wavelength (OPDW) Nd:GdVO4/Nd:YVO4 laser at 1341 and 1342 nm on the 4F3/2 →4I13/2 transition was realized using in-band laser diode (LD) pumping with tunable wavelength from 909.40 to 915.02 nm for the first time. The operating temperature of the LD and the position of the pump beam waist were optimized to achieve high efficiency and balanced output powers of the OPDW laser. The OPDW laser at 1341 and 1342 nm was obtained with the highest total output power of 6.15 W and the power ratio of 1:1. The highest total slope efficiency and total optical-to-optical conversion efficiency with respect to the absorbed pump power at 913.61 nm were 34.9% and 32.0%, respectively. The OPDW laser at 1341 and 1342 nm have important application prospects in the fields of laser medicine, scientific research and terahertz radiation.